2017
DOI: 10.1186/s12944-017-0483-9
|View full text |Cite
|
Sign up to set email alerts
|

Liver phospholipids fatty acids composition in response to different types of diets in rats of both sexes

Abstract: BackgroundDietary intake influence changes in fatty acids (FA) profiles in liver which plays a central role in fatty acid metabolism, triacylglycerol synthesis and energy homeostasis. We investigated the effects of 4-weeks treatment with milk- and fish-based diet, on plasma biochemical parameters and FA composition of liver phospholipids (PL) in rats of both sexes.MethodsAdult, 4 months old, Wistar rats of both sexes, were fed with different types of diets: standard, milk-based and fish-based, during 4 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
1
11
0
1
Order By: Relevance
“…Moreover, sex-dependent activation of biological pathways in response to a specific diet has been previously described. For instance, milk-based diets influence liver enzymes quantity in males rats, while fish-based diets have a stronger effect on liver fatty acid composition in females, showing that basal differences in liver lipid composition between male and females are modulated by diet [ 62 ]. Moreover, in vitro studies reveal a sex-specific drug metabolism in the liver of goats [ 63 ] and nutritional challenges can influence sex-specific metabolic modifications in adult sheep [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sex-dependent activation of biological pathways in response to a specific diet has been previously described. For instance, milk-based diets influence liver enzymes quantity in males rats, while fish-based diets have a stronger effect on liver fatty acid composition in females, showing that basal differences in liver lipid composition between male and females are modulated by diet [ 62 ]. Moreover, in vitro studies reveal a sex-specific drug metabolism in the liver of goats [ 63 ] and nutritional challenges can influence sex-specific metabolic modifications in adult sheep [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using genetically defined IVs as proxies of modifiable exposure avoids confounding by environmental factors, is not subject to reverse causality and can inform on life-long exposure [10] , [11] . Since studies have shown that FA intake influences plasma levels of FAs in theory MR makes an attractive strategy to link dietary FA to CRC risk [12] , [13] .…”
Section: Introductionmentioning
confidence: 99%
“…We observed sexspecific changes in FA profile. In case of fish-based diet, there was more pronounced increase in the concentration of omega-3 FA (both total and individual FA) in female comparing with the male rats 18 . Considering this and the fact that polyunsaturated FA could be used as indirect measure of lipid peroxidation (as the most prone FA to lipid peroxida-Vidović N, et al Vojnosanit Pregl 2020; 77(6): 641-646. tion), we assumed that the changes in lipid peroxidation and other parameters of oxidative stress would be more pronounced in female rats 25 .…”
Section: Discussionmentioning
confidence: 87%
“…The formulation of rat chow was made by the Department of Animal Nutrition and Botany, Faculty of Veterinary Medicine, University of Belgrade, Serbia. A detailed analytical characterisation of food (rat chow), its chemical composition, respectively is given in previously published article 18 .…”
Section: Animals and Treatmentsmentioning
confidence: 99%